Tinkering with cognitive gadgets: Cultural evolutionary psychology meets active inference. (2019) - Badcock, Paul Benjamin; Constant, Axel; Ramstead, Maxwell James Désormeau
Abstract: Cognitive Gadgets offers a new, convincing perspective on the origins of our distinctive cognitive faculties, coupled with a clear, innovative research program. Although we broadly endorse Heyes' ideas, we raise some concerns about her characterisation of evolutionary psychology and the relationship between biology and culture, before discussing the potential fruits of examining cognitive gadgets through the lens of active inference.